Cangrelor, Tirofiban, and Chewed or Standard Prasugrel Regimens in Patients With ST-Segment-Elevation Myocardial Infarction: Primary Results of the FABOLUS-FASTER Trial - Gargiulo, Giuseppe; Esposito, Giovanni; Avvedimento, Marisa; Nagler, Michael; Minuz, Pietro; Campo, Gianluca; Gragnano, Felice; Manavifar, Negar; Piccolo, Raffaele; Tebaldi, Matteo; Cirillo, Plinio; Hunziker, Lukas; et al. (Circulation (New York, N.Y.), 2020)
Standard administration of newer oral P2Y inhibitors, including prasugrel or ticagrelor, provides suboptimal early inhibition of platelet aggregation (IPA) in patients with ST-segment-elevation myocardial infarction undergoing primary percutaneous coronary intervention. We aimed to investigate the effects of cangrelor, tirofiban, and prasugrel, administered as chewed or integral loading dose, on IPA in patients undergoing primary percutaneous coronary intervention. The FABOLUS-FASTER trial (Facilitation Through Aggrastat or Cangrelor Bolus and Infusion Over Prasugrel: A Multicenter Randomized Open-Label Trial in Patients with ST-Elevation Myocardial Infarction Referred for Primary Percutaneous Intervention) is an investigator-initiated, multicenter, open-label, randomized study. A total of 122 P2Y -naive patients with ST-segment-elevation myocardial infarction were randomly allocated (1:1:1) to cangrelor (n=40), tirofiban (n=40) (both administered as bolus and 2-hour infusion followed by 60 mg of prasugrel), or 60-mg loading dose of prasugrel (n=42). The latter group underwent an immediate 1:1 subrandomization to chewed (n=21) or integral (n=21) tablets administration. The trial was powered to test 3 hypotheses (noninferiority of cangrelor compared with tirofiban using a noninferiority margin of 9%, superiority of both tirofiban and cangrelor compared with chewed prasugrel, and superiority of chewed prasugrel as compared with integral prasugrel, each with α=0.016 for the primary end point, which was 30-minute IPA at light transmittance aggregometry in response to 20 μmol/L adenosine diphosphate. At 30 minutes, cangrelor did not satisfy noninferiority compared with tirofiban, which yielded superior IPA over cangrelor (95.0±8.9 versus 34.1±22.5; <0.001). Cangrelor or tirofiban were both superior to chewed prasugrel (IPA, 10.5±11.0; <0.001 for both comparisons), which did not provide higher IPA over integral prasugrel (6.3±11.4; =0.47), despite yielding higher prasugrel active metabolite concentration (ng/mL; 62.3±82.6 versus 17.1±43.5; =0.016). Cangrelor provided inferior IPA compared with tirofiban; both treatments yielded greater IPA compared with chewed prasugrel, which led to higher active metabolite concentration but not greater IPA compared with integral prasugrel. Registration: URL: https://www.clinicaltrials.gov; Unique identifier: NCT02978040; URL: https://www.clinicaltrialsregister.eu; EudraCT 2017-001065-24.